IDNLearn.com: Your go-to resource for finding precise and accurate answers. Ask anything and receive immediate, well-informed answers from our dedicated community of experts.
Sagot :
9t +7 = 0
t-1 =0
solve for both giving
t = -7/9
t = 1
then we have to plug that back in to u which is x^2
so x^2 = (-7/9)^2 = -1
x^2 = 1
if any doubt leave a comment
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Discover the answers you need at IDNLearn.com. Thank you for visiting, and we hope to see you again for more solutions.